Building regulations in brief - Tricker, Ray (Elsevier Butterworth-Heinemann, 2011)
The most popular and affordable guide to the building regulations, Building Regulations in Brief is updated regularly to reflect constant changes. Now in its 6th edition, it has sold over 25,000 copies since its first publication in 2003. This new edition includes the latest on all the significant amendments to Building Regulations, Planning Permission and the Approved Documents between 2007 and April 2010 and includes changes to Parts A, B, D, E, F, G, H, J, L, M, and N. The changes to Part G of Building Regulations (formerly titled "Hygiene" and now renamed "Sanitation, hot water and water efficiency") which came into effect on 6 April 2010 are also included. The no-nonsense approach has made it a firm favourite with all involved in the building industry including designers, building surveyors and inspectors, students and architects. A ready reference giving practical information, it enables compliance in the simplest and most cost-effective manner possible. Building Regulations in Brief cuts through the confusion to explain the meaning of the regulations, their history, current status, requirements, associated documentation and how local authorities view their importance, as well as emphasizing the benefits and requirements of each regulation. It's an essential purchase for anyone needing to comply with the Building Regs.